Investigating the microorganisms-calcium sulfate interaction in reverse osmosis systems using SEM-EDX technique. Issue 4 (August 2020) - Ashfaq, Mohammad Y.; Al-Ghouti, Mohammad A.; Al Disi, Zulfa A.; Zouari, Nabil
Graphical abstract: Highlights: Microorganism-mineral interactions can affect the membrane fouling in SWRO. Bacteria present in seawater can induce gypsum precipitation on RO membranes. Crystals' morphology varies from needle like to floral structures under SEM-EDX. The presence of divalent ions in a medium enhances microbial growth rates. Abstract: Membrane fouling affects the performance of membrane technologies such as reverse osmosis (RO), in water treatments and desalination industries. The membrane fouling is a multifaceted phenomenon and various components of feedwater like organic and inorganic substances, and microorganisms interact with each other to further complicate and intensify the membrane fouling. In this research, the interaction between microorganisms and calcium sulfate (mineral chosen as a model scaling) was investigated. Using scanning electron microscopy – energy dispersive x-ray (SEM-EDX) technique, it was found that the variety of microorganisms present in seawater were able to form calcium sulfate crystals on the RO membrane, although no precipitation occurred under abiotic conditions (i.e. in control samples). The results of SEM-EDX were further confirmed by quantitative analysis of precipitation through ion chromatography (IC) technique, and it was found that the concentration of calcium ions remaining in the bacteria-containing medium was significantly lower than that of controls at 95 % confidence level. Furthermore, the kinetics of biomineralization and the effect of different concentrations of calcium and sulfate ions was investigated. It was found that the bacteria were able to form needle-like crystals even at the lowest concentration (Ca 2+ =20 mM) and at the lowest incubation times (i.e. 1 day) studied. On the other hand, the effect of calcium ions on bacterial growth was also investigated and it was noted that the presence of ions resulted in a statistically significant increase in growth rates of bacteria, showing their potential to enhance biofouling rates.